The Influence Of Financial Technology (Fintech) On The Performance Of Msmes In Palembang City, Mediated By Financial Literacy - Indah Diana; Dewi Sartika; Sulaiman Helmi; Fitriasuri (Equivalent : Journal of Economic, Accounting and Management, 2026)
The development of financial technology (fintech) provides significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve their business performance. However, optimal fintech utilization is strongly influenced by the level of financial literacy of MSMEs. This study aims to analyze the influence of financial technology on the performance of MSMEs in Palembang City, with financial literacy as a mediating variable. The research method used a quantitative approach, collecting data through questionnaires from 100 MSMEs in Palembang City. The data analysis technique used path analysis or Structural Equation Modeling (SEM). The results show that financial technology has a positive and significant effect on MSME performance. In addition, financial technology also has a positive effect on financial literacy, and financial literacy has been proven to have a positive effect on MSME performance. Financial literacy can significantly mediate the influence of financial technology on MSME performance. These findings indicate that improving the financial literacy of MSMEs is crucial for the effective use of fintech and optimal impact on business performance. This research is expected to serve as a reference for the government and stakeholders in formulating policies for developing MSMEs based on financial technology.